2011
DOI: 10.21608/ejana.2011.3662
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Cyclophosphamide on the Postnatal Development of the Ovary of the Albino Rat

Abstract: Background: Cyclophosphamide is the most widely used alkylating agent in the treatment of haematological malignancies. On the other hand, cyclophosphamide has adverse effects on the fertility of both sexes. Aim of the work: The present work was done to study the histological and stereological changes in the developing ovary of the albino rat after a period of treatment with cyclophosphamide and the effect of rehabilitation after stopping the drug. Materials and Methods: Thirty-six immature female rats (newborn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 24 publications
0
1
0
Order By: Relevance
“…In the present work, the busulfan treated group showed remnants of some cytoplasmic organelles of the granulosa cells with dilated and destructed rough endoplasmic reticulum, swollen mitochondria with destruction of their cristae. These findings were explained by some authors [32] who suggested that mitochondrial apoptotic pathway was initiated either by damaging stimuli such as oxidative stress or DNA damage by DNA alkylation.…”
Section: Discussionmentioning
confidence: 97%
“…In the present work, the busulfan treated group showed remnants of some cytoplasmic organelles of the granulosa cells with dilated and destructed rough endoplasmic reticulum, swollen mitochondria with destruction of their cristae. These findings were explained by some authors [32] who suggested that mitochondrial apoptotic pathway was initiated either by damaging stimuli such as oxidative stress or DNA damage by DNA alkylation.…”
Section: Discussionmentioning
confidence: 97%